Volcanism and the atmosphere: the potential role of the atmosphere in unlocking the reactivity of volcanic emissions - Mather, T (Royal Society Publishing, 2008)
Recent measurements of reactive trace gas species in volcanic plumes have offered intriguing hints at the chemistry occurring in the hot environment at volcanic vents. This has led to the recognition that volcanic vents should be regarded not only as passive sources of volcanic gases to the atmosphere, but also as 'reaction vessels' that unlock otherwise inert volcanic and atmospheric gas species. The atypical conditions created by the mixing of ambient atmosphere with the hot gases emitted from magma give rise to elevated concentrations of otherwise unexpected chemical compounds. Rapid cooling of this mixture allows these species to persist into the environment, with important consequences for gas plume chemistry and impacts. This paper discusses some examples of the implications of these high-temperature interactions in terms of nitrogen, halogen and sulphur chemistry, and their consequences in terms of the global fixed nitrogen budget, volcanically induced ozone destruction and particle fluxes to the atmosphere. Volcanically initiated atmospheric chemistry was likely to have been particularly important before biological (and latterly anthropogenic) processes started to dominate many geochemical cycles, with important consequences in terms of the evolution of the nitrogen cycle and the role of particles in modulating the Earth's climate.